Hubungan Persepsi Ibu Hamil Tentang Kehamilan Dengan Tingkat Kecerdasan Emosional - Urva Susanti; Misrawati '; Wasisto Utomo (Jurnal Ners Indonesia, 2012)
The aim of this research to determine the relationship between perception of pregnant mother about pregnancy and emotionalintelegence. The research method used in this study was descriptive correlation. The research was conducted at PuskesmasUmban Sari of Subdistrict Rumbai with 50 pregnant women, by using technique of accidental sampling. Research instrumentused was questionnairs which have been tested for their validity and reliability. The research analysis used was univariat andbivariate analysis by using chi square test. The result of this research indicate that most respondents have the positif perceptionabout pregnancy and the number of pregnant women who have good emotional intelligence are similar to those who have bademotional intelligence. The statistical analysis using chi square got p value (0,023) < (0.05), which means Ho was rejectedand that there is relationship between pregnant womens, perception about pregnancy and emotional intelligence. Based on thisresult it is a positive suggested to health provider to motivate the pregnant women to look into pregnancy as matter wherepregnancy is a present from God which have to be accepted by controlling their psychical condition through good emotionalintelligence.Key words : perception of pregnant mother, pregnancy emotional intelligence